Cationic Europium Complexes for Visualizing Fluctuations in Mitochondrial ATP Levels in Living Cells. Issue 42 (28th June 2018) - Mailhot, Romain; Traviss‐Pollard, Thomas; Pal, Robert; Butler, Stephen J.
Abstract: The ability to study cellular metabolism and enzymatic processes involving adenosine triphosphate (ATP) is impeded by the lack of imaging probes capable of signalling the concentration and distribution of intracellular ATP rapidly, with high sensitivity. We report here the first example of a luminescent lanthanide complex capable of visualizing changes in the concentration of ATP in the mitochondria of living cells. Four cationic europium(III) complexes [Eu.1 –4 ] + have been synthesized and their binding capabilities towards nucleoside polyphosphate anions examined in aqueous solution at physiological pH. Complexes [Eu.1 ] + and [Eu.3 ] + bearing hydrogen bond donor groups in the pendant arms showed excellent discrimination between ATP, ADP and monophosphate species. Complex [Eu.3 ] + showed relatively strong binding to ATP (log K a =5.8), providing a rapid, long‐lived luminescent signal that enabled its detection in a highly competitive aqueous medium containing biologically relevant concentrations of Mg 2+, ADP, GTP, UTP and human serum albumin. This Eu III complex responds linearly to ATP within the physiological concentration range (1–5 mm ), and was used to continuously monitor the apyrase‐catalyzed hydrolysis of ATP to ADP in vitro. We demonstrate that [Eu.3 ] + can permeate mammalian (NIH‐3T3) cells efficiently and localize to the mitochondria selectively, permitting real‐time visualization of elevated mitochondrial ATP levels following treatment with a broad spectrum kinase inhibitor, staurosporine, as well as depleted ATP levels upon treatment with potassium cyanide under glucose starvation conditions. Abstract : A short series of cationic Eu III complexes for visualising dynamic changes in the concentration of ATP within the mitochondria of living cells is reported. Complex [Eu.3 ] + binds reversibly to ATP and responds linearly to this anion within the physiological range (1–5 mm ). The probe was used to visualize elevated ATP levels following treatment with a broad‐spectrum kinase inhibitor, staurosporine, as well as depleted ATP levels upon treatment with KCN under glucose starvation conditions.